Assessing sustainability focus across global banks - Ushasi Sengupta; Himadri Sikhar Pramanik; Sayantan Datta; Swayambhu Dutta; Sankhanilam Dasgupta; Manish Kirtania (Development Engineering, 2023)
Global banks play intermediary and even direct roles in achievement of the UN Sustainable Development Goals (SDGs). However, developmental progress is complex to measure due to siloed, varied and even non-transparent, ambiguous, non-standardized ways of calibration and reporting. This research explores public disclosures (sustainability, CSR, and annual reports, press releases, website, and others) of fifty banks across nine geo-segments over five calendar years (2018-2023). Inductive methods, co-word assessments, content analysis are deployed to develop qualitative commentaries indicating geo-specific performances of the banks. The research findings indicate goal-specific attribution and discovery of motives and initiatives. This validates how motives in embracing the SDGs vary and relate to achievement of - (A) core business objectives; (B) support and financing of other industries, organizations, and governments in sustainable initiatives; and (C) corporate citizenship, altruistic and ethical considerations. Methodological approaches to calibrate findings across seventeen SDGs help identify benchmark practices, understand complementary actions, and required focus for banks and other industries. This is relevant to geo-specific sustainability challenges, trade-offs, and requirements. The findings can guide public policies and regulations, empower banks and other institutions to accelerate awareness and evaluate effectiveness towards sustainable developments.
Keywords: 330; Bank; Sustainable development goals; Measurement; Motives; Qualitative research; Geo-segment